The utility of multiparametric MRI to characterize hypoxic tumor subvolumes in comparison to FMISO PET/CT. Consequences for diagnosis and chemoradiation treatment planning in head and neck cancer. (September 2020) - Wiedenmann, Nicole; Grosu, Anca-Ligia; Büchert, Martin; Rischke, Hans C.; Ruf, Juri; Bielak, Lars; Majerus, Liette; Rühle, Alexander; Bamberg, Fabian; Baltas, Dimos; Hennig, Jürgen; Mix, Michael; et al.
Highlights: Hypoxic tumor volumes showed lower diffusion and perfusion at baseline and early into treatment in comparison to non-hypoxic areas. Distinct differences in the hypoxia dynamics and hypoxia reduction were noted between primary tumors and lymph nodes. ADC was significantly lower in hypoxic than non-hypoxic tumor areas during the early phases of radiotherapy and increased towards treatment completion in both primary tumors and lymph nodes. Perfusion limitations were more prevalent in hypoxic primary tumors than in hypoxic lymph node metastases. Abstract: Background and Purpose: Hypoxia is an essential metabolic marker that determines chemo- and radiation resistance in head-and-neck squamous cell carcinoma (HNSCC) patients. Our exploratory analysis aimed to identify multiparametric MRI (mpMRI) parameters linked to hypoxia that might be used as surrogate for [ 18 F]FMISO-PET in diagnosis and chemoradiation treatment (CRT) of HNSCC. Materials and Methods: 21 patients undergoing definitive CRT for HNSCC were prospectively imaged with serial [ 18 F]FMISO-PET and 3 Tesla mpMRI for T1- and T2-weighted and dynamic contrast-enhanced perfusion and diffusion-weighted measurements (k trans, ve, kep, ADC) in weeks 0, 2 and 5 and FDG-PET in week 0. [ 18 F]FMISO-PET-derived hypoxic subvolumes (HSV) and complementary non-hypoxic subvolumes (nonHSV) were created for tumor and lymph nodes and projected on the mpMRI scans after PET/MRI co-registration. MpMRI and [ 18 F]FMISO-PET parameters within HSVs and nonHSVs were statistically compared. Results: FMISO-PET-based HSVs of the primary tumors on MRI were characterized by lower ADC at all time points ( p = 0.012 at baseline; p = 0.015 in week 2) and reduced interstitial space volume fraction ve and perfusion k trans at baseline ( p = 0.006, p = 0.047) compared to nonHSVs. Hypoxic lymph nodes were characterized by significantly lower ADC values at baseline ( p = 0.039), but not at later time points and a reduction in k trans -based perfusion at week 2 ( p = 0.018). Conclusion: MpMRI parameters differ significantly between hypoxic and non-hypoxic tumor regions, defined on FMISO-PET/CT as gold standard and might represent surrogate markers for tumor hypoxia. These findings suggest that mpMRI may be useful in the future as a surrogate modality for hypoxia imaging in order to personalize CRT.